Malaysian’s attitudes towards the importance of insurance in personal financial planning / Siti Norhazwani Mohd Hasim - Mohd Hasim, Siti Norhazwani (2011)
This exploratory study focused on attitude of Malaysian‟s toward the importance of insurance in personal financial planning. Target respondents were in Kuang, Selangor which is 3400 populations. Drawing from theoretical foundation, an empirical survey was conducted among 341 people in Kuang, Selangor insuring and non insuring to gauge their awareness level and general attitudes towards insurance in personal financial planning. The sample consisted of 341 respondents collected through random sampling of probability sampling technique. There were statistically significant differences between males and females in the attitudes toward the importance of insurance in personal financial planning. Female are often more aware on insurance in personal financial planning so that their attitude are more positive rather than male. Furthermore, the attitudes are negative because of are mirrored through low patronage of insurance services and unsatisfied within insurance transaction. It discusses such social cultural factors that account for these attitudes and what role marketing strategies and related party such as insurance company can play to change such negative attitude. The findings present different demographical factors and their attitudes towards insurance in personal financial planning. It is expected that findings from such survey would constitute vital input for insurers in designing marketing strategies that would further stimulate and boost patronage and perception of insurance services. At the same time gave an idea to related party such as insurance company and government to take action on how to increase positive attitude toward the importance of insurance in personal financial planning.